The Association for the Development of Education in Africa - Independent Evaluation Group (World Bank, Washington, DC, 2017)
The Association for the Development of Education in Africa (ADEA) was established by the World Bank in 1988 in response to an influential policy paper issued the previous year on education in sub-Saharan Africa, education in Sub-Saharan Africa: policies for adjustment, revitalization, and expansion. Originally the association was created as an informal network of development agencies in Africa (Donors to African Education, DAE) having an informal secretariat at the World Bank, but by 1994 (when its principles of association were formalized) it grew into a professional association of both development agencies and African ministries of education. In a further evolution, in 1997 it changed its name to the ADEA. This Regional Program Review (RPR) assesses the quality and independence of the 2005 evaluation of ADEA, provides a second opinion on the effectiveness of the program, assesses the performance of the Bank as a partner in the program, and draws lessons for the future operation of the program. Independent Evaluation Group (IEG) chose ADEA for an RPR because of the importance of the sector in the Bank's mission of poverty reduction, because IEG has done relatively few reviews of regional programs, and because IEG had not conducted a global or regional program review in the field of education before.